STUDI PEMBUATAN LEM SEDERHANA DARI BAHAN KARET KREP DAN PELARUT METHYL ETYL KETONE - Suharyanto Suharyanto (Politeknik ATK Yogyakarta, 2014)
This research aims to make simple glue from rubber material and Methyl Ethyl Ketone crepe as a solvent and fiyer tagky comaron or resin; with 5 simple glue models: Model 1, Model 2, Model 3, Model 4, and Model 5. This strategy is applied in order to try to manufacture simple glue made from rubber crepe which is abundant and easy to obtain. This research developed simple glue from rubber crepe and Methyl Ethyl Ketone solvent to get various glue with good quality. This research made simple glue to assemble the leather to be folded, glued and sticked, in which the application is in leather samples and testing method used peel strength or adhesion of the two materials glued together using glue. This research used method of cutting crepe into small pieces which then placed in a glass jar, weighed 2 kg with comparison 1; 1.5; 2; and 2.5 to Methyl Ethyl Ketone and added comaron or resin material in order to have more glue adhesion or better adhesiveness. In conclusion, the a simple glue from crepe rubber material can be used to fold, glue and stick the upper of leather shoes.